Study of biological safety of camel milk after treatment with different antibiotics - Zauresh Bilal; Farida Amutova; Zaira Kabdullina; Dariga Utemuratova; Askar Kondybayev; Shynar Akhmetsadykova; Zhaidar Musayev; Nurlan Akhmetsadykov; Bernard Faye; Gaukhar Konuspayeva (PLoS ONE, 2025)
The use of antibiotics in camels is generally based on the doses applied to cattle, despite the known differences in plasma pharmacokinetics between camel and cattle. The demand for camel milk increased due to the belief that traditional camel farming practices produce safe milk with health benefits. For assessing the importance of antibiotic residues in camel milk and to propose a convenient withdrawal period, a trial was conducted on 10 lactating camels (7–12 years old; 450 kg life weight (LW), 7–8 liter of milk production per day) at mid-lactation receiving an injection of 40 mL of Pen-strep® (benzylpenicillin-procaine 200,000 IU/1 ml and dihydrostreptomycin sulfate 200 mg/1 ml) and Nitox® (oxytetracycline dihydrate 200 mg/1 ml). The antibiotic residues were measured in the milk 30 min after injection then on day 1, 2, 3, 7, 9, 14, 19, 24 and 56 by using HPLC-MS/MS. Results showed that penicillin’s mean residual concentration (0.3 ± 0.013 mg/kg) remained 7.5 times above the maximum residue limit (MRL) even on 56th day. In contrast, streptomycin fell below the MRL within 30 minutes and averaged 1 µg/kg by day 56. Oxytetracycline levels exceeded the MRL (0.1 mg/kg) until day 14 but dropped to a safe level of 0.018 ± 0.01 mg/kg by day 24. In conclusion, the decline in streptomycin concentration post-injection appeared rapid and efficient, the elimination of penicillin and tetracycline was slow. These preliminary results lead to considering the necessity to adapt the waiting time to the dairy camel.